2013
DOI: 10.1073/pnas.1214387110
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of adult rod photoreceptors prevents retinal degeneration

Abstract: A prime goal of regenerative medicine is to direct cell fates in a therapeutically useful manner. Retinitis pigmentosa is one of the most common degenerative diseases of the eye and is associated with early rod photoreceptor death followed by secondary cone degeneration. We hypothesized that converting adult rods into cones, via knockdown of the rod photoreceptor determinant Nrl, could make the cells resistant to the effects of mutations in rodspecific genes, thereby preventing secondary cone loss. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 48 publications
(54 reference statements)
3
74
2
Order By: Relevance
“…Inspiringly, an increasing number of reports have demonstrated that lineage reprogramming can be achieved in vivo Inagawa et al, 2012;Jayawardena et al, 2012;Li et al, 2014b;Mathison et al, 2012;Montana et al, 2013;Niu et al, 2013;Qian et al, 2012;Rouaux and Arlotta, 2013;Song et al, 2012;Torper et al, 2013;Zhou et al, 2008). Recently, it has been reported that glial cells, especially astrocytes, can be converted into functional neuroblasts or neurons in vivo Niu et al, 2013;Torper et al, 2013).…”
Section: Strategies To Produce Large Numbers Of Induced Cells For Tramentioning
confidence: 95%
“…Inspiringly, an increasing number of reports have demonstrated that lineage reprogramming can be achieved in vivo Inagawa et al, 2012;Jayawardena et al, 2012;Li et al, 2014b;Mathison et al, 2012;Montana et al, 2013;Niu et al, 2013;Qian et al, 2012;Rouaux and Arlotta, 2013;Song et al, 2012;Torper et al, 2013;Zhou et al, 2008). Recently, it has been reported that glial cells, especially astrocytes, can be converted into functional neuroblasts or neurons in vivo Niu et al, 2013;Torper et al, 2013).…”
Section: Strategies To Produce Large Numbers Of Induced Cells For Tramentioning
confidence: 95%
“…Accumulating evidence indicates that mature retinal neurons are plastic and can undergo fate reprogramming. For example, ablating the Nrl gene in mature rod photoreceptors results in partial transformation of rod cells toward a cone cell fate, accompanied by altered rod nuclear morphology and enhanced cell survival (53). It is possible that Jak-STAT signaling directly influences the chromatin structure of photoreceptor cells in a cell autonomous fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support this bipotent precursor model: (1) some rod and cone marker [i.e. Nrl and Thrβ2 (TRβ2)] overlap has been observed during development (Ng et al, 2011); (2) Nrl expression in developing cones can partially convert cells to a rod identity (Oh et al, 2007); and (3) removing Nrl from adult rods can partially convert them into cones (Montana et al, 2013). An alternative explanation (Fig.…”
Section: Transcriptional Network Regulating Photoreceptor Identitymentioning
confidence: 99%